Perbedaan Pemberian Kabohidrat dan Protein Telur Terhadap Kenaikan Berat Badan Pada Anak Balita Gizi Buruk - Pujiati Setyaningsih; Mokhamad Arifin; Eka Budiarto (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2017)
This study aims to determine differences in the provision of carbohydrates and protein eggs to weight gain in malnourished children under five in the region of Pekalongan. This research was using quasi experiment design. Sampling using purposive sampling method, obtained 28 samples divided into two groups. Independent t-test showed that there were the influence of carbohydrate (p-value = 0.0025) and egg protein (p-value = 0.0055) to the weight gain of malnourished children under five years. Mann-withney test showed there was a difference between carbohydrates and egg protein to weight gain in malnourished children under five (p = 0.491). The results of the research can be used as guidance of giving nutrition for under five children, especially malnutrition toddlers.